Unexpected Reactivity of [(η5‐1, 2, 4‐tBu3C5H2)Ni(η3‐P3)] towards Main Group Nucleophiles and by Reduction. Issue 27 (21st April 2016) - Mädl, Eric; Balázs, Gábor; Peresypkina, Eugenia V.; Scheer, Manfred
Abstract: The reduction of [Cp′′′Ni(η 3 ‐P3 )] (1 ; Cp′′′=η 5 ‐1, 2, 4‐ t Bu3 C5 H2 ) with potassium produces the complex anion [(Cp′′′Ni)2 (μ, η 2:2 ‐P8 )] 2− (2 ), which contains a realgar‐like P8 unit. The anionic triple‐decker sandwich complex [(Cp′′′Ni)2 (μ, η 3:3 ‐P3 )] − (3 ) with a cyclo‐P3 middle deck is obtained when1 is treated with NaNH2 as a nucleophile. Na[3 ] can subsequently be oxidized with AgOTf to the neutral triple‐decker complex [(Cp′′′Ni)2 (μ, η 3:3 ‐P3 )] (4 ). In contrast, 1 reacts with LiPPh2 to give the anionic compound [(Cp′′′Ni)2 (μ, η 2:2 ‐P6 PPh2 )] − (5 ), a complex containing a bicyclic P7 fragment capped by two Cp′′′Ni units. Protonation of Li[5 ] with HBF4 leads to the neutral complex [(Cp′′′Ni)2 (μ, η 2:2 ‐(HP6 PPh2 )] (6 ). Adding LiNMe2 to1 results in [Cp′′′Ni(η 2 ‐P3 NMe2 )] − (7 ) becoming accessible, a complex which forms as a result of nucleophilic attack at the cyclo‐P3 ring of1 . The complexes K2 [2 ], Na[3 ], 4, 6, and Li[7 ] were fully characterized and their structures determined by single‐crystal X‐ray diffraction. Abstract : Stacking the deck : The reaction of [(η 5 ‐1, 2, 4‐ t Bu3 C5 H2 )Ni(η 3 ‐P3 )] with potassium leads to the formation of a realgar‐like P8 ligand. Triple‐decker sandwich complexes with a P3 middle deck or unprecedented bicyclic P7 ligands are formed with nucleophiles.